2007
DOI: 10.1152/ajpgi.00419.2006
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress stimulates colonic motility via central corticotropin-releasing factor and peripheral 5-HT3 receptors in conscious rats

Abstract: Although restraint stress accelerates colonic transit via a central corticotropin-releasing factor (CRF), the precise mechanism still remains unclear. We tested the hypothesis that restraint stress and central CRF stimulate colonic motility and transit via a vagal pathway and 5-HT3 receptors of the proximal colon in rats. 51Cr was injected via the catheter positioned in the proximal colon to measure colonic transit. The rats were subjected to a restraint stress for 90 min or received intracisternal injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 37 publications
6
85
1
1
Order By: Relevance
“…We have recently shown that intraluminal administration of ondansetron had no effects on basal activity and that restraint stress significantly augmented colonic motility in conscious rats (40). Current study also showed that restraint stress significantly increased the motor activity of the distal colon.…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…We have recently shown that intraluminal administration of ondansetron had no effects on basal activity and that restraint stress significantly augmented colonic motility in conscious rats (40). Current study also showed that restraint stress significantly increased the motor activity of the distal colon.…”
Section: Resultssupporting
confidence: 47%
“…Stress-induced simulation of colonic motility is antagonized by a systemic treatment with 5-HT 3 receptor antagonists (36). We have recently showed that restraint stress augmented colonic motility and increased the luminal release of 5-HT of the proximal colon in rats (40). Thus, luminally released 5-HT has an important role in stress-induced stimulation of colonic motility.…”
Section: Discussionmentioning
confidence: 98%
“…Gastric emptying of solid and liquid meals is delayed by acute restraint stress in rodents [5] . In contrast, acute restraint stress accelerates colonic transit in rats [6] and mice [7] . There are two distinct CRF receptors, subtype 1 (CRF type1) and subtype 2 (CRF type2).…”
mentioning
confidence: 85%
“…Delayed gastric emptying induced by acute restraint stress is mediated via central CRF2 receptors [5] . In contrast, accelerated colonic transit induced by acute restraint stress is mediated via central CRF1 receptors in rats [6] . Acute restraint stress stimulates central CRF2 receptors and sympathetic pathway, resulting in delayed gastric emptying [5] ( Figure 1), while acute restraint stress stimulates central CRF1 receptors and parasympathetic pathways (vagal nerve and pelvic nerve), resulting in acceleration of colonic transit in rats [6] ( Figure 1).…”
mentioning
confidence: 86%
“…14,15 Unlike the slower motility in the stomach and small intestine, stressor exposure tends to enhance motility in the colon. 16 In addition to affecting these secretory and motor responses, the physiological stress response can also affect protective barriers in the intestines. Stress exposure can significantly alter mucous levels in the colon, as well as the levels of secretory immunoglobulin A.…”
Section: Stress the Stress Response And Impact On Gut Physiologicalmentioning
confidence: 99%